Switched-capacitor-convertors based on fractal design for output power management of triboelectric nanogenerator - Wenlin Liu (Nature Portfolio, 2020)
Power management systems are urgently needed for maximally utilizing the energy generated from triboelectric energy devices. Here, the authors report a fractal-designed switched-capacitor-convertor as a high efficiency power management strategy for triboelectric nanogenerators.